Operational Determinants of Profitability: Evidence from Nepalese Development Banks - Narendra Sejuwal,; Makshindra Thapa,; Prakash Shrestha, (Journal of Business and Social Sciences, 2025)
This study examines the profitability of Nepalese development banks predicted by operational factors (including liquidity ratio, operating efficiency, capital adequacy ratio, and non-performing assets). Descriptive and causal-comparative research designs were used to predict the effects of the operational factors on profitability measured in return on equity. The quantitative data of the study variables using panel data from nine NEPSE listed development banks covering 10-years period (F/Y 2014/15 to 2023/24) are employed.  The result of multiple regression analysis demonstrates substantial negative effect of liquidity ratio and non-performing assets on return on equity, reaffirming the trade-off between liquidity and profitability as well as the crucial role of credit risk management. On the other hand, even while CAR levels are significantly beyond regulatory minimums, ER and CA show no statistically significant effect on profitability. These findings raise questions about the generalizability of banking theories and highlight the necessity of regulatory frameworks that are sensitive to context and recognize the dual goals of development banks—financial sustainability and developmental lending. Furthermore, the study supports efforts to strengthen this crucial area of Nepal's financial architecture by providing empirical information to help development bank management formulate policies and make strategic decisions.